The Influence of Basic Psychological Needs Satisfaction on Well-Being: A Study on Higher Education Faculty in the New Normal - Janine Marie Balajadia; Maria Micole Veatrizze Dy; Lukas Pariñas; Christine Leila Taguba; Alessandra Grace Tan; Maxine Therese Tuazon; Jerome Patrick Uy; Genejane Adarlo (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The world has entered a new normal in response to the crisis caused by the COVID-19 pandemic. This new normal has unique challenges and opportunities for the faculty, as physical campuses have gradually re-opened for teaching and learning. Although a growing amount of research has shown a relationship between the extent of basic psychological needs satisfaction and the state of well-being in diverse populations, studies focused on faculty in the new normal remain limited. An online survey of 100 faculty members from an institution of Catholic higher education in the Philippines was conducted in the latter half of 2022 to examine this relationship. The results of this study showed that satisfying the basic psychological needs of faculty during the new normal can contribute significantly to their well-being. These results can inform higher education institutions about how they can best support their faculty in the new normal and promote student learning.